The Relationship of Stress Level to the Incidence of Pityriasis Capitis (Dandruff) in Students at SMK Panca Karsa Sungai Pinyuh - S, Amalia Putri; Sinaga, Jojor Putrini; Liana, Delima Fajar (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
Stress is a condition of disturbing the balance of organisms that involves physiological or psychological tension caused by internal or external factors. Stress is one of the factors that can trigger the incidence of Pityriasis capitis. The level of stress is closely related to the high activity of sebaceous glands which results in changes in temperature and humidity on the scalp. To know the relationship between stress level with the incidence of Pityriasis capitis (dandruff) among female student of Vocational and Pre-Professional High School Panca Karsa Sungai Pinyuh. Observational analytic research with approach design research type cross-sectional. A total of 50 people was involved in this experiment. Independent variable was stress level, and dependent variable was Pityriasis capitis (dandruff) incidence among female students at Vocational and Pre-Professional high school Panca Karsa Sungai Pinyuh. From 50 people, it was found that Pityriasis capitis occurred respondents with normal stress level about 42,9%. The results of the Kolmogorov-Smirnov comparative test showed a significance value of p = 0.591 (p> 0.05) indicating that there was no significant relationship between stress level and Pityriasis capitis (dandruff). There is no relationship between the level of stress with the incidence of Pityriasis Capitis (dandruff) among female students at Vocational and Pre-Professional high school Panca Karsa Sungai Pinyuh.